Endoscopic endonasal orbital cavernous hemangioma resection: global experience in techniques and outcomes. Issue 2 (1st December 2015) - Bleier, Benjamin S.; Castelnuovo, Paolo; Battaglia, Paolo; Turri‐Zanoni, Mario; Dallan, Iacopo; Metson, Ralph; Sedaghat, Ahmad R.; Stefko, S. Tonya; Gardner, Paul A.; Snyderman, Carl H.; Nogueira, Joao Flavio; Ramakrishnan, Vijay R.; et al.
Abstract : Background: Endoscopic orbital surgery represents the next frontier in endonasal surgery. The current literature is largely composed of small, heterogeneous, case series with little consensus regarding optimal techniques. The purpose of this study was to combine the experience of multiple international centers to create a composite of the global experience on the endoscopic management of a single type of tumor, the orbital cavernous hemangioma (OCH). Methods: This was a retrospective study of techniques for endoscopic OCH resection from 6 centers on 3 continents. Only primary data from strictly endoscopic resection of OCHs were included. Responses were analyzed to qualitatively identify points of both consensus and variability among the different groups. Results: Data for a total of 23 patients, 10 (43.5%) male and 13 (56.5%) female were collected. The majority of lesions were intraconal (60.9%). The mean ± standard deviation (SD) surgical time was 150.7 ± 75.0 minutes with a mean blood loss of 82.7 ± 49.6 mL. Binarial approaches (26.1%) were used exclusively in the setting of intraconal lesions, which were associated with a higher rate of incomplete resection (31.3%), postoperative diplopia (25.0%), and the need for reconstruction (37.5%) than extraconal lesions. Orthotropia and symmetric orbital appearance were achieved in 60.9% and 78.3% of cases, respectively. Conclusion: Extraconal lesions were managed similarly; however, greater variability was evident for intraconal lesions. These included the laterality and number of hands in the approach, methods of medial rectus retraction, and the need for reconstruction. The increased technical complexity and disparity of techniques in addressing intraconal OCHs suggests that continued research into the optimal management of this subclass of lesions is of significant priority.